ENHANCING PVDF POLYMER PROPERTIES VIA VARIED BARIUM TITANATE MORPHOLOGIES AND SYNTHESIS TECHNIQUES: REVIEW - Abdulelah, Haider; Sweah, Zainab J; Fouad, Firas; Modhi, Hussein (Journal for Technology and Science, 2024)
Background: Polyvinylidene fluoride (PVDF) is widely utilized in electronic devices due to its piezoelectric properties, which can be enhanced through the incorporation of barium titanate (BT). However, the impact of various fabrication methods on the crystallinity and beta-phase content of PVDF/BT nanocomposites remains underexplored. Specific Background: Different manufacturing techniques, including 3D printing, electrospinning, solvent casting, and compression molding, influence the structural and functional properties of PVDF/BT composites. The crystallinity and beta-phase content of PVDF are critical for optimizing the dielectric and piezoelectric performance of these materials. Knowledge Gap: There is a lack of comprehensive studies comparing the effects of these fabrication techniques on the crystallinity and beta-phase enhancement of PVDF/BT composites, particularly concerning their dielectric, piezoelectric, and mechanical properties. Aims: This study aimed to investigate the impact of integrating BT into PVDF using various fabrication methods on the crystallinity and beta-phase formation. The goal was to determine how these modifications influence the material’s structural characteristics and, consequently, its electronic properties. Results: X-ray Diffraction (XRD) and Fourier-Transform Infrared Spectroscopy (FTIR) analyses revealed that 3D printing and electrospinning methods significantly enhanced the beta-phase content and crystallinity of PVDF/BT composites compared to solvent casting and compression molding. Scanning Electron Microscopy (SEM) confirmed improved morphological features in the PVDF matrix with these techniques. Novelty: This study provides new insights into how different fabrication methods can optimize the crystallinity and beta-phase of PVDF/BT nanocomposites, which are crucial for enhancing piezoelectric performance. Implications: The findings suggest that 3D printing and electrospinning are superior to traditional methods for fabricating PVDF/BT composites with enhanced piezoelectric properties. These results can guide the development of more efficient electronic devices by selecting appropriate fabrication techniques to achieve desired material properties.